Pregnancy in a Young Patient with Metastatic HER2-Positive Breast Cancer—Between Fear of Recurrence and Desire to Procreate - Cristina Marinela Oprean; Andrei Dorin Ciocoiu; Nusa Alina Segarceanu; Diana Moldoveanu; Alexandra Stan; Teodora Hoinoiu; Ioana Chiorean-Cojocaru; Daciana Grujic; Adelina Stefanut; Daniel Pit; Alis Dema (Current Oncology, 2023)
Breast cancer is the most frequent neoplasm among women and the second leading cause of death by cancer. It is the most frequent cancer diagnosed during pregnancy. Pregnancy-associated breast cancer is defined as breast cancer that is diagnosed during pregnancy and/or in the postpartum period. Data about young women with metastatic HER2-positive cancer who desire a pregnancy are scarce. The medical attitude in these clinical situations is difficult and nonstandardized. We present the case of a 31-year-old premenopausal woman diagnosed in December 2016 with a stage IV Luminal HER2-positive metastatic breast cancer (pT2 N0 M1 hep). The patient was initially treated by surgery in a conservative manner. Postoperatively, the presence of liver metastases was found by CT investigation. Consequently, line I treatment (docetaxel l75 mg/m² iv; trastuzumab 600 mg/5 mL sq) and ovarian drug suppression (Goserelin 3.6 mg sq at 28 days) was administered. After nine cycles of treatment, the patient’s liver metastases had a partial response to the therapy. Despite having a favorable disease evolution and a strong desire to procreate, the patient vehemently refused to continue any oncological treatment. The psychiatric consult highlighted an anxious and depressive reaction for which individual and couple psychotherapy sessions were recommended. After 10 months from the interruption of the oncological treatment, the patient appeared with an evolving pregnancy of 15 weeks. An abdominal ultrasound revealed the presence of multiple liver metastases. Knowing all the possible effects, the patient consciously decided to postpone the proposed second-line treatment. In August 2018, the patient was admitted in the emergency department with malaise, diffuse abdominal pain and hepatic failure. Abdominal ultrasound found a 21-week-old pregnancy which had stopped in evolution, multiple liver metastases and ascites in large quantity. She was transferred to the ICU department where she perished just a few hours later. Conclusions/Discussion: From a psychological standpoint, the patient had an emotional hardship to make the transition from the status of a healthy person to the status of a sick person. Consequently, she entered a process of emotional protection of the positive cognitive distortion type, which favored the decision to abandon treatment and try to complete the pregnancy to the detriment of her own survival. The patient delayed the initiation of oncological treatment in pregnancy until it was too late. The consequence of this delay in treatment led to the death of the mother and fetus. A multidisciplinary team worked to provide this patient with the best medical care and psychological assistance throughout the course of the disease.